Preparation method of carbon nanotube cement-based waterproof material

By filling multi-walled carbon nanotubes with rare earth elements and composited with aluminum elements and silicon sol, the problem of insufficient elastic modulus and tensile strength of waterproof concrete materials in the prior art is solved, and efficient waterproof performance and excellent mechanical properties are achieved.

CN119822758AActive Publication Date: 2025-04-15SHANDONG BOXIONG CONSTR ENG CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510326122.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-15
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

While improving the waterproof performance of concrete, it is difficult to improve its elastic modulus and tensile strength.

Method used

Multi-walled carbon nanotubes are filled with rare earth elements and composited with aluminum elements and silica sol, and added to the waterproof concrete material as raw material components. The method includes heat treatment of multi-walled carbon nanotubes, ultrasonic impregnation and mixing with silica sol to prepare carbon nanotube composite silica sol.

Benefits of technology

While ensuring waterproof performance, the elastic modulus and tensile strength of the waterproof material are significantly improved, and the wear resistance and gas permeability of the material are also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a preparation method of a carbon nanotube cement-based waterproof material, and belongs to the field of building waterproof concrete materials. The preparation method comprises the following steps: filling multi-walled carbon nanotubes, preparing carbon nanotube composite silica sol, and preparing the waterproof material. The prepared waterproof material is excellent in mechanical property, the compressive strength, the breaking strength, the splitting tensile strength and the static compressive elastic modulus of the waterproof material are detected according to the method in GB / T50081-2019, and the compressive strength is 47.4 MPa to 48.8 MPa, the breaking strength is 17.1 MPa to 17.5 MPa, the splitting tensile strength is 4.3 MPa to 4.5 MPa, and the static compressive elastic modulus is 52.3 GPa to 53.0 GPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a carbon nanotube cement-based waterproof material, and belongs to the field of building waterproof concrete materials. Background Art

[0002] Concrete is rich in raw materials. It not only has good plasticity and durability, but also can meet the needs of various structural projects. It is currently the most widely used and most used engineering material. However, factors such as the design of concrete structure and mix ratio, the selection of concrete materials, and concrete construction and on-site maintenance can easily cause concrete cracks and affect the strength of the entire building structure. For this reason, researchers consider adding particles, fibers, active powders and other materials to concrete to improve the performance of concrete, among which the research on nanomaterials is more concerned.

[0003] Concrete is composed of cement, water and other materials mixed with high-quality aggregates of the same particle size or discontinuous grading. There are inevitably micropores and microcracks on the surface, and it has a certain porosity. These structural defects provide channels for water molecules to penetrate into the interior of the concrete. If used in roads, it can achieve certain drainage, sound absorption and noise reduction functions, but it does not have a waterproof effect and cannot be used as a building waterproof material. If the concrete material is made to have a certain waterproof effect by adding certain substances, then the low-cost advantage of concrete as a waterproof material can enable it to be more widely used.

[0004] Nanomaterials have smaller volumes, better optical, thermal, electrical and stronger mechanical properties. It is this series of excellent properties that provide strong theoretical and technical support for the study of the application of nanomaterials in cement-based composites. Studies have found that the addition of nanomaterials such as carbon nanotubes effectively improves the performance of cement-based composites. Not only can they fill the microporous structure of cement, but carbon nanotubes can also produce chemical forces with the surface of concrete hydration products, limiting the spread of nano-scale cracks, making the microstructure of concrete more compact, and thus improving the waterproof performance of concrete.

[0005] CN102603235A discloses a carbon nanotube cement-based waterproof material and a preparation method thereof. Carbon nanotubes are added to the raw material components of concrete, so that the concrete can obtain higher waterproof performance. The carbon nanotubes used in the invention are multi-walled carbon nanotubes (multi-walled carbon nanotubes). Compared with single-walled carbon nanotubes (single-walled carbon nanotubes), the price is lower and the performance in some aspects is better. For example, multi-walled carbon nanotubes have more defects in the axial direction and have different degrees of concave-convex phenomena, which will increase the strength of the concrete material, and the degree of increase is higher than that of adding single-walled carbon nanotubes. However, due to the structural defects of multi-walled carbon nanotubes, the elastic properties and tensile properties of single-walled carbon nanotubes themselves are better than those of multi-walled carbon nanotubes. When multi-walled carbon nanotubes are added to concrete, the elastic modulus and tensile strength of the concrete will be lower. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the defects of the prior art by filling multi-walled carbon nanotubes with rare earth elements, compounding them with aluminum elements and silica sol, and adding them as raw material components to waterproof concrete materials, thereby ensuring the waterproof performance of the material while improving the elastic modulus and tensile strength of the material.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a carbon nanotube cement-based waterproof material, the preparation method comprising filling with multi-walled carbon nanotubes, preparing carbon nanotube composite silica sol, and preparing the waterproof material.

[0008] The following are further improvements to the above technical solution: The multi-walled carbon nanotube filling method comprises placing the multi-walled carbon nanotube in a nitrogen atmosphere, controlling the heating rate to be 4.5-5.5°C / min, raising the temperature to 405-425°C, heat-treating the multi-walled carbon nanotube for 85-95 minutes, and controlling the cooling rate to be 2.5-3.5°C / min after the treatment, cooling the multi-walled carbon nanotube to 60-70°C, and keeping the temperature, and then immersing the kept multi-walled carbon nanotube in a cerium sulfate solution, controlling the frequency to be 50-70kHz, and performing ultrasound for 12-20 minutes. After the ultrasound is finished, filtering and drying are performed to obtain the multi-walled carbon nanotube filled with rare earth elements; The mass ratio of the multi-walled carbon nanotubes to the cerium sulfate solution is 1:4.5-5.5; The multi-walled carbon nanotubes have a diameter of 70-100 nm and a length of 200-300 μm; The concentration of cerium element in the cerium sulfate solution is 8-12 g / L, and the solvent of the solution is 0.15 mol / L sulfuric acid.

[0009] The method for preparing the carbon nanotube composite silica sol is as follows: in a nitrogen atmosphere, multi-walled carbon nanotubes filled with rare earth elements are mixed with a trimethylaluminum solution, and stirred for 18-25 minutes. After the stirring is completed, the nitrogen atmosphere is maintained, and the heating rate is controlled to be 4.5-5.5° C. / min, and the temperature is raised to 825-870° C., and sintered for 110-130 minutes. After the sintering is completed, alumina-coated multi-walled carbon nanotubes are obtained, and after cooling to room temperature, the multi-walled carbon nanotubes are mixed with silica sol, and stirred at a speed of 50-90 r / min. While stirring, the temperature is controlled to be 100° C., and the water in the silica sol is evaporated until the water content is 0, so as to obtain the carbon nanotube composite silica sol; The mass ratio of the rare earth element-filled multi-walled carbon nanotubes to the trimethylaluminum solution is 5:10-14; The concentration of the trimethylaluminum solution is 20-30wt%, and the solvent is n-hexane; The mass ratio of the alumina-coated multi-walled carbon nanotubes to the silica sol is 5:6.5-7.5; The concentration of the silica sol is 15-25wt%, the particle size of the colloidal particles is 12-20nm, and the solvent is deionized water.

[0010] The method for preparing the waterproof material comprises: pouring cement, fine sand, quartz sand and fly ash into a mortar mixer and dry-mixing them for 8-12 minutes, then adding water, a water reducing agent and a defoaming agent into the mixer, continuing to stir for 13-17 minutes, and finally adding carbon nanotube composite silica sol, continuing to stir for 22-28 minutes, and after the stirring is completed, pouring into a mold, and curing to obtain a carbon nanotube cement-based waterproof material; The mass ratio of the cement, fine sand, quartz sand, fly ash, water, water reducing agent, defoaming agent and carbon nanotube composite silica sol is 700-800:575-625:325-375:110-130:475-550:10-12:4.5-5.5:8-10; The model of the cement is P·O42.5 grade ordinary Portland cement; The fineness modulus of the fine sand is 2.37 and the apparent density is 2587 g / m 3 ; The particle size of the quartz sand is 0.45-0.55 mm; The particle size of the fly ash is 150-200 μm; The water reducer is a polycarboxylic acid water reducer, model number is XCA-100; The defoamer is a silicone polyether defoamer, and its model is Deqian Defom6800.

[0011] Compared with the prior art, the present invention achieves the following beneficial effects: The waterproof material prepared by the present invention has excellent mechanical properties. According to the method in GB / T50081-2019, the compressive strength, flexural strength, splitting tensile strength, and static compressive elastic modulus of the waterproof material are tested. The compressive strength is 47.4-48.8MPa, the flexural strength is 17.1-17.5MPa, the splitting tensile strength is 4.3-4.5MPa, and the static compressive elastic modulus is 52.3-53.0GPa; The waterproof material prepared by the present invention has excellent waterproof performance. According to the method in GB / T50081-2019, the water absorption rate of the waterproof material is detected, and the water absorption rate is 0.54-0.58%; according to the method in GB / T50082-2024, the step-by-step pressurization method is adopted to detect the water permeability resistance of the waterproof material, and the maximum pressure when water seepage occurs is used as an indicator, and the water permeability resistance is 1.7-1.8MPa; according to the method in GB / T50082-2024, the electric flux method is adopted to detect the chloride ion permeability resistance of the waterproof material, and the electric flux is used as an indicator, and the 28d electric flux is 37-41C; The waterproof material prepared by the present invention has good wear resistance. According to the method in GB / T50081-2019, the wear resistance of the waterproof material is tested by the abrasion method, and the abrasion is 0.011-0.014 kg / m 2 ; The waterproof material prepared by the present invention has a low expansion coefficient and is less affected by thermal expansion and contraction. According to the method in GB / T50081-2019, the linear expansion coefficient of the waterproof material is tested, and the linear expansion coefficient is (0.7-0.8)×10 -6 ; The waterproof material prepared by the present invention has good gas permeability resistance. According to the method in GB / T50082-2024, the apparent gas permeability coefficient of nitrogen under a pressure of 0.4 MPa is tested, and the gas permeability coefficient is (4.1-4.4)×10 -18 . DETAILED DESCRIPTION

[0012] Example 1 (1) Multi-walled carbon nanotube filling The multi-walled carbon nanotubes are placed in a nitrogen atmosphere, the heating rate is controlled to be 5°C / min, the temperature is raised to 415°C, the multi-walled carbon nanotubes are heat-treated, the heat treatment time is 90 minutes, and after the treatment, the cooling rate is controlled to be 3°C / min, the multi-walled carbon nanotubes are cooled to 65°C, and the heat is kept, and then the heat-preserved multi-walled carbon nanotubes are immersed in a cerium sulfate solution, the frequency is controlled to be 60kHz, and the ultrasound is performed for 15 minutes. After the ultrasound is completed, the multi-walled carbon nanotubes are filtered and dried to obtain rare earth element-filled multi-walled carbon nanotubes; The mass ratio of the multi-walled carbon nanotubes to the cerium sulfate solution is 1:5; The multi-walled carbon nanotubes have a diameter of 80 nm and a length of 240 μm; The concentration of cerium element in the cerium sulfate solution is 10 g / L, and the solvent of the solution is 0.15 mol / L sulfuric acid.

[0013] (2) Preparation of carbon nanotube composite silica sol In a nitrogen atmosphere, a rare earth element-filled multi-walled carbon nanotube is mixed with a trimethylaluminum solution and stirred for 20 minutes. After the stirring is completed, the nitrogen atmosphere is maintained, and the heating rate is controlled to be 5°C / min, and the temperature is raised to 850°C for sintering. The sintering time is 120 minutes. After the sintering is completed, alumina-coated multi-walled carbon nanotubes are obtained. After cooling to room temperature, the multi-walled carbon nanotubes are mixed with silica sol and stirred at a speed of 60r / min. While stirring, the temperature is controlled to be 100°C, and the water in the silica sol is evaporated until the water content is 0, thereby obtaining a carbon nanotube composite silica sol; The mass ratio of the rare earth element-filled multi-walled carbon nanotubes to the trimethylaluminum solution is 5:12; The concentration of the trimethylaluminum solution is 25wt%, and the solvent is n-hexane; The mass ratio of the alumina-coated multi-walled carbon nanotubes to the silica sol is 5:7; The concentration of the silica sol is 20wt%, the particle size of the colloidal particles is 15nm, and the solvent is deionized water.

[0014] (3) Preparation of waterproof materials Pour cement, fine sand, quartz sand and fly ash into a mortar mixer and dry-mix them for 10 minutes, then add water, a water reducing agent and a defoaming agent into the mixer and continue to stir for 15 minutes, finally add carbon nanotube composite silica sol and continue to stir for 25 minutes, after stirring, pour into a mold, and then obtain a carbon nanotube cement-based waterproof material after curing; The mass ratio of the cement, fine sand, quartz sand, fly ash, water, water reducing agent, defoaming agent and carbon nanotube composite silica sol is 750:600:350:120:520:11:5:9; The model of the cement is P·O42.5 grade ordinary Portland cement; The fineness modulus of the fine sand is 2.37 and the apparent density is 2587 g / m 3 ; The particle size of the quartz sand is 0.50 mm; The particle size of the fly ash is 170 μm; The water reducer is a polycarboxylic acid water reducer, model number is XCA-100; The defoamer is a silicone polyether defoamer, and its model is Deqian Defom6800.

[0015] Example 2 (1) Multi-walled carbon nanotube filling The multi-walled carbon nanotubes are placed in a nitrogen atmosphere, the heating rate is controlled to be 4.5°C / min, the temperature is raised to 425°C, the multi-walled carbon nanotubes are heat-treated, the heat treatment time is 85 minutes, and after the treatment is completed, the cooling rate is controlled to be 2.5°C / min, the multi-walled carbon nanotubes are cooled to 60°C, and the heat is kept, and then the heat-preserved multi-walled carbon nanotubes are immersed in a cerium sulfate solution, the frequency is controlled to be 50kHz, and the ultrasound is performed for 20 minutes. After the ultrasound is completed, the multi-walled carbon nanotubes are filtered and dried to obtain rare earth element-filled multi-walled carbon nanotubes; The mass ratio of the multi-walled carbon nanotubes to the cerium sulfate solution is 1:4.5; The multi-walled carbon nanotubes have a diameter of 70 nm and a length of 200 μm; The concentration of cerium element in the cerium sulfate solution is 8 g / L, and the solvent of the solution is 0.15 mol / L sulfuric acid.

[0016] (2) Preparation of carbon nanotube composite silica sol In a nitrogen atmosphere, a rare earth element-filled multi-walled carbon nanotube is mixed with a trimethylaluminum solution and stirred for 18 minutes. After stirring, the nitrogen atmosphere is maintained, and the heating rate is controlled to be 4.5°C / min, and the temperature is raised to 870°C for sintering. The sintering time is 110 minutes. After sintering, alumina-coated multi-walled carbon nanotubes are obtained. After cooling to room temperature, the multi-walled carbon nanotubes are mixed with silica sol and stirred at a speed of 50 r / min. While stirring, the temperature is controlled to be 100°C, and the water in the silica sol is evaporated until the water content is 0, thereby obtaining a carbon nanotube composite silica sol; The mass ratio of the rare earth element-filled multi-walled carbon nanotubes to the trimethylaluminum solution is 5:10; The concentration of the trimethylaluminum solution is 30wt%, and the solvent is n-hexane; The mass ratio of the alumina-coated multi-walled carbon nanotubes to the silica sol is 5:6.5; The concentration of the silica sol is 25 wt %, the particle size of the colloidal particles is 12 nm, and the solvent is deionized water.

[0017] (3) Preparation of waterproof materials Pour cement, fine sand, quartz sand and fly ash into a mortar mixer and dry-mix them for 8 minutes, then add water, a water reducing agent and a defoaming agent into the mixer and continue to stir for 17 minutes, finally add carbon nanotube composite silica sol and continue to stir for 22 minutes, after stirring, pour into a mold, and then obtain a carbon nanotube cement-based waterproof material after curing; The mass ratio of the cement, fine sand, quartz sand, fly ash, water, water reducing agent, defoaming agent and carbon nanotube composite silica sol is 700:575:325:110:475:10:4.5:8; The model of the cement is P·O42.5 grade ordinary Portland cement; The fineness modulus of the fine sand is 2.37 and the apparent density is 2587 g / m 3 ; The particle size of the quartz sand is 0.45 mm; The particle size of the fly ash is 150 μm; The water reducer is a polycarboxylic acid water reducer, model number is XCA-100; The defoamer is a silicone polyether defoamer, and its model is Deqian Defom6800.

[0018] Example 3 (1) Multi-walled carbon nanotube filling The multi-walled carbon nanotubes are placed in a nitrogen atmosphere, the heating rate is controlled to be 5.5°C / min, the temperature is raised to 405°C, the multi-walled carbon nanotubes are heat-treated, the heat treatment time is 95 minutes, and after the treatment, the cooling rate is controlled to be 3.5°C / min, the multi-walled carbon nanotubes are cooled to 70°C, and the heat is kept, and then the heat-preserved multi-walled carbon nanotubes are immersed in a cerium sulfate solution, the frequency is controlled to be 70kHz, and the ultrasound is performed for 12 minutes. After the ultrasound is completed, the multi-walled carbon nanotubes are filtered and dried to obtain rare earth element-filled multi-walled carbon nanotubes; The mass ratio of the multi-walled carbon nanotubes to the cerium sulfate solution is 1:5.5; The multi-walled carbon nanotube has a diameter of 100 nm and a length of 300 μm; The concentration of cerium element in the cerium sulfate solution is 12 g / L, and the solvent of the solution is 0.15 mol / L sulfuric acid.

[0019] (2) Preparation of carbon nanotube composite silica sol In a nitrogen atmosphere, a rare earth element-filled multi-walled carbon nanotube is mixed with a trimethylaluminum solution and stirred for 25 minutes. After stirring, the nitrogen atmosphere is maintained and the heating rate is controlled to be 5.5°C / min. The temperature is raised to 825°C for sintering. The sintering time is 130 minutes. After sintering, alumina-coated multi-walled carbon nanotubes are obtained. After cooling to room temperature, the multi-walled carbon nanotubes are mixed with silica sol and stirred at a speed of 90 r / min. While stirring, the temperature is controlled to be 100°C to evaporate the water in the silica sol until the water content is 0, thereby obtaining a carbon nanotube composite silica sol. The mass ratio of the rare earth element-filled multi-walled carbon nanotubes to the trimethylaluminum solution is 5:14; The concentration of the trimethylaluminum solution is 20wt%, and the solvent is n-hexane; The mass ratio of the alumina-coated multi-walled carbon nanotubes to the silica sol is 5:7.5; The concentration of the silica sol is 15 wt %, the particle size of the colloidal particles is 20 nm, and the solvent is deionized water.

[0020] (3) Preparation of waterproof materials Pour cement, fine sand, quartz sand and fly ash into a mortar mixer and dry-mix them for 12 minutes, then add water, a water reducing agent and a defoaming agent into the mixer and continue to stir for 13 minutes, finally add carbon nanotube composite silica sol and continue to stir for 28 minutes, after stirring, pour into a mold, and then obtain a carbon nanotube cement-based waterproof material after curing; The mass ratio of the cement, fine sand, quartz sand, fly ash, water, water reducing agent, defoaming agent and carbon nanotube composite silica sol is 800:625:375:130:550:12:5.5:10; The model of the cement is P·O42.5 grade ordinary Portland cement; The fineness modulus of the fine sand is 2.37 and the apparent density is 2587 g / m 3 ; The particle size of the quartz sand is 0.55 mm; The particle size of the fly ash is 200 μm; The water reducer is a polycarboxylic acid water reducer, model number is XCA-100; The defoamer is a silicone polyether defoamer, and its model is Deqian Defom6800.

[0021] Comparative Example 1 Different from Example 1, the multi-walled carbon nanotube filling step is omitted, and the untreated multi-walled carbon nanotubes are directly used for the step of preparing carbon nanotube composite silica sol. When the dosage remains unchanged, the remaining steps remain unchanged to prepare the waterproof material.

[0022] Comparative Example 2 Different from Example 1, the step of preparing carbon nanotube composite silica sol is omitted, and the multi-walled carbon nanotubes filled with rare earth elements obtained in the multi-walled carbon nanotube filling step are directly used as the raw material of the waterproof material. The waterproof material is prepared while keeping the remaining steps unchanged while keeping the dosage unchanged.

[0023] Test Example 1 Mechanical properties test of waterproof materials The compressive strength, flexural strength, splitting tensile strength and static compressive elastic modulus of the waterproof materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested according to the method in GB / T50081-2019. The results are shown in Table 1.

[0024] Table 1 In Example 1-3, rare earth element multi-walled carbon nanotubes are used for filling, and then the nanotubes are compounded with aluminum and silica sol, and the nanotubes are added as raw material components to waterproof concrete materials. The prepared waterproof materials have relatively excellent mechanical properties, and the compressive strength, flexural strength, splitting tensile strength, and static compressive elastic modulus are all relatively high; Comparative Example 1 omitted the multi-walled carbon nanotube filling step, and directly carried out the step of preparing carbon nanotube composite silica sol with the untreated multi-walled carbon nanotubes. The mechanical properties of the waterproof material finally prepared decreased, especially the compressive strength, splitting tensile strength, and static compressive elastic modulus decreased particularly seriously, and the flexural strength also decreased to a large extent; In Comparative Example 2, the step of preparing carbon nanotube composite silica sol is omitted, and the multi-walled carbon nanotubes filled with rare earth elements obtained in the multi-walled carbon nanotube filling step are directly used as the raw material of the waterproof material to prepare the waterproof material. The mechanical properties of the waterproof material finally prepared decrease, especially the decrease in flexural strength is particularly serious, and the compressive strength, splitting tensile strength, and static compressive elastic modulus also decrease to a large extent.

[0025] Test Example 2 Waterproof performance test of waterproof material The water absorption rate of the waterproof materials prepared in Examples 1-3 and Comparative Examples 1-2 was tested according to the method in GB / T50081-2019. The water resistance of the waterproof materials was tested by the step-by-step pressurization method according to the method in GB / T50082-2024, with the maximum pressure when water seepage occurred as an indicator. The resistance of the waterproof materials to chloride ion permeability was tested by the electric flux method according to the method in GB / T50082-2024, with the electric flux as an indicator. The results are shown in Table 2.

[0026] Table 2 Example 1-3 uses rare earth element multi-walled carbon nanotubes for filling, and then compounds them with aluminum elements and silica sol, and adds them as raw material components to waterproof concrete materials. The prepared waterproof material has relatively excellent waterproof performance, not only has low water absorption, can maintain anti-seepage performance under high water pressure, but also has good resistance to chloride ion permeability and low electric flux; Comparative Example 1 omitted the multi-walled carbon nanotube filling step, and directly carried out the step of preparing carbon nanotube composite silica sol with the untreated multi-walled carbon nanotubes. The waterproof performance of the waterproof material finally prepared decreased, especially the water absorption rate increased more seriously, the water seepage pressure decreased seriously, and the electric flux also increased to a large extent, and the resistance to chloride ion permeability was poor. In Comparative Example 2, the step of preparing carbon nanotube composite silica sol is omitted, and the multi-walled carbon nanotubes filled with rare earth elements obtained in the multi-walled carbon nanotube filling step are directly used as the raw material of the waterproof material to prepare the waterproof material. The waterproof performance of the waterproof material finally prepared decreases, especially the chloride ion permeability decreases particularly seriously, the electric flux increases seriously, the water absorption rate also increases to a large extent, and the anti-water seepage pressure decreases to a large extent.

[0027] Test Example 3: Waterproof material wear resistance test The waterproof materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested for wear resistance using the abrasion method according to the method in GB / T50081-2019. The results are shown in Table 3.

[0028] Table 3 Example 1-3 uses rare earth element multi-walled carbon nanotubes for filling, and then compounds them with aluminum element and silica sol, and adds them as raw material components to waterproof concrete materials. The prepared waterproof material has relatively excellent wear resistance and low wear per unit area. In Comparative Example 1, the multi-walled carbon nanotube filling step was omitted, and the untreated multi-walled carbon nanotubes were directly used for the step of preparing the carbon nanotube composite silica sol. The wear resistance of the waterproof material finally prepared decreased, and the wear loss per unit area increased seriously. In Comparative Example 2, the step of preparing carbon nanotube composite silica sol is omitted, and the multi-walled carbon nanotubes filled with rare earth elements obtained in the multi-walled carbon nanotube filling step are directly used as the raw material of the waterproof material to prepare the waterproof material. The wear resistance of the waterproof material finally prepared decreases, and the wear per unit area increases to a large extent.

[0029] Test Example 4: Waterproof material expansion coefficient test The linear expansion coefficient of the waterproof materials prepared in Examples 1-3 and Comparative Examples 1-2 was tested according to the method in GB / T50081-2019. The results are shown in Table 4.

[0030] Table 4 In Example 1-3, rare earth element multi-walled carbon nanotubes are used for filling, and then the nanotubes are compounded with aluminum and silica sol, and the nanotubes are added as raw material components to waterproof concrete materials. The prepared waterproof material has a lower expansion coefficient and is less affected by thermal expansion and contraction. Comparative Example 1 omits the multi-walled carbon nanotube filling step, and directly uses the untreated multi-walled carbon nanotubes to prepare the carbon nanotube composite silica sol step. The expansion coefficient of the waterproof material finally prepared increases to a certain extent, and is greatly affected by thermal expansion and contraction. In Comparative Example 2, the step of preparing carbon nanotube composite silica sol is omitted, and the multi-walled carbon nanotubes filled with rare earth elements obtained in the multi-walled carbon nanotube filling step are directly used as the raw material of the waterproof material to prepare the waterproof material. The expansion coefficient of the waterproof material finally prepared increases seriously and is greatly affected by thermal expansion and contraction.

[0031] Test Example 5: Gas Permeability Test of Waterproof Materials The waterproof materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested according to the method in GB / T50082-2024, with nitrogen as the test gas and the gas line pressure set to 0.4 MPa. The apparent gas permeability coefficients at this pressure were tested. The results are shown in Table 5.

[0032] Table 5 In Example 1-3, rare earth element multi-walled carbon nanotubes are used for filling, and then the nanotubes are compounded with aluminum and silica sol, and the nanotubes are added as raw material components to waterproof concrete materials. The prepared waterproof material has a lower gas permeability coefficient, and the interior of the waterproof material is relatively dense. Comparative Example 1 omitted the multi-walled carbon nanotube filling step, and directly carried out the step of preparing carbon nanotube composite silica sol with the untreated multi-walled carbon nanotubes. The gas permeability coefficient of the final preparation increased to a certain extent, and the internal compactness of the waterproof material was poor. In Comparative Example 2, the step of preparing carbon nanotube composite silica sol is omitted, and the multi-walled carbon nanotubes filled with rare earth elements obtained in the multi-walled carbon nanotube filling step are directly used as the raw material of the waterproof material to prepare the waterproof material. The gas permeability coefficient of the final preparation increases seriously, and the internal density of the waterproof material is poor.

Claims

1. A method for preparing a carbon nanotube cement-based waterproof material, characterized in that: The preparation method includes filling with multi-walled carbon nanotubes, preparing carbon nanotube composite silica sol, and preparing waterproof material; The multi-walled carbon nanotube filling method comprises placing the multi-walled carbon nanotube in a nitrogen atmosphere, heating the multi-walled carbon nanotube to 405-425° C., heat-treating the multi-walled carbon nanotube for 85-95 minutes, cooling the multi-walled carbon nanotube to 60-70° C. after the treatment, and keeping the temperature, then immersing the kept multi-walled carbon nanotube in a cerium sulfate solution, performing ultrasound, and after the ultrasound, filtering and drying to obtain the multi-walled carbon nanotube filled with rare earth elements; The mass ratio of the multi-walled carbon nanotubes to the cerium sulfate solution is 1:4.5-5.5; The concentration of cerium element in the cerium sulfate solution is 8-12 g / L; The method for preparing the carbon nanotube composite silica sol comprises: mixing and stirring multi-walled carbon nanotubes filled with rare earth elements and trimethylaluminum solution in a nitrogen atmosphere; maintaining the nitrogen atmosphere, heating to 825-870° C., and sintering for 110-130 minutes; after sintering, alumina-coated multi-walled carbon nanotubes are obtained; cooling the multi-walled carbon nanotubes to room temperature, mixing the multi-walled carbon nanotubes with silica sol, and continuously stirring to evaporate water to obtain the carbon nanotube composite silica sol; The mass ratio of the rare earth element-filled multi-walled carbon nanotubes to the trimethylaluminum solution is 5:10-14; The mass ratio of the alumina-coated multi-walled carbon nanotubes to the silica sol is 5:6.5-7.5; The method for preparing the waterproof material comprises mixing and stirring the raw materials according to the steps, pouring the raw materials into a mold after stirring, and finally curing to obtain a carbon nanotube cement-based waterproof material; The raw materials include cement, fine sand, quartz sand, fly ash, water, water reducing agent, defoaming agent and carbon nanotube composite silica sol, and the mass ratio thereof is 700-800:575-625:325-375:110-130:475-550:10-12:4.5-5.5:8-10.

2. The method for preparing a carbon nanotube cement-based waterproof material according to claim 1, characterized in that: In the multi-walled carbon nanotube filling method, the heating method is to control the heating rate to 4.5-5.5°C / min; the cooling method is to control the cooling rate to 2.5-3.5°C / min; the ultrasonic method is to control the frequency to 50-70kHz, perform ultrasonication, and the ultrasonication time is 12-20min.

3. The method for preparing a carbon nanotube cement-based waterproof material according to claim 1, characterized in that: In the multi-walled carbon nanotube filling method, the solvent of the cerium sulfate solution is 0.15 mol / L sulfuric acid; the diameter of the multi-walled carbon nanotube is 70-100 nm, and the length is 200-300 μm.

4. The method for preparing a carbon nanotube cement-based waterproof material according to claim 1, characterized in that: In the method for preparing carbon nanotube composite silica sol, the heating method is to control the heating rate to 4.5-5.5°C / min; after the multi-walled carbon nanotubes filled with rare earth elements are mixed with the trimethylaluminum solution, the stirring time is 18-25min, and the method for stirring to evaporate water is to stir at a speed of 50-90r / min, and control the temperature to 100°C while stirring, so as to evaporate the water in the silica sol until the water content is 0.

5. The method for preparing a carbon nanotube cement-based waterproof material according to claim 1, characterized in that: In the method for preparing carbon nanotube composite silica sol, the concentration of trimethylaluminum solution is 20-30wt%, and the solvent is n-hexane; the concentration of silica sol is 15-25wt%, the particle size of colloidal particles is 12-20nm, and the solvent is deionized water.

6. The method for preparing a carbon nanotube cement-based waterproof material according to claim 1, characterized in that: In the method for preparing the waterproof material, the cement type is P·O42.5 grade ordinary Portland cement; the fineness modulus of the fine sand is 2.37, and the apparent density is 2587g / m 3 ; The particle size of quartz sand is 0.45-0.55mm; the particle size of fly ash is 150-200μm; the water reducer is a polycarboxylic acid type water reducer, model XCA-100; the defoamer is a silicone polyether type defoamer, model Deqian Defom6800.

7. The method for preparing a carbon nanotube cement-based waterproof material according to claim 1, characterized in that: In the method for preparing the waterproof material, the raw materials are mixed and stirred separately according to the steps, cement, fine sand, quartz sand and fly ash are dry-mixed for 8-12 minutes, water, water reducing agent and defoaming agent are added to the mixer, stirring is continued for 13-17 minutes, and finally carbon nanotube composite silica sol is added and stirring is continued for 22-28 minutes.

Citation Information

Patent Citations

  • Carbon nano-tube cement-based waterproof material and preparation method thereof

    CN102603235A

  • Ceria / multi-walled carbon nano-tube composite material

    CN101559360A

  • Graphene / carbon nanotube cement-based waterproof material and preparation method thereof

    CN107010893A

  • High-strength corrosion-resistant carbon nanotube modified concrete and preparation method thereof

    CN112679129A

  • Cement-based composite material based on multi-walled carbon nanotubes and preparation method of cement-based composite material

    CN114149211A